Strong towns : a bottom-up revolution to rebuild American prosperity - Marohn, Charles L., Jr (John Wiley & Sons, Inc., 2019)
"Strong Towns: A Bottom-Up Revolution to Build American Prosperity is a book of forward-thinking ideas that breaks with modern wisdom to present a new vision of urban development in the United States. Presenting the foundational ideas of the Strong Towns movement he co-founded, Charles Marohn explains why cities of all sizes continue to struggle to meet their basic needs, and reveals the new paradigm that can solve this longstanding problem."--Amazon.